Atmospheric circulation in the Indian Ocean sector of East Antarctica over the last 200 years according to chemical studies of snow‑firn cover - E. Yu. Osipov; O. P. Osipova; L. P. Golobokova; T. V. Khodzher (Лëд и снег)
Spatial and temporal variability of a sea‑salt aerosol (Na+) concentration was investigated in snow‑firn cores and snow pits taken at four sites of the Indian Ocean sector of the East Antarctica (along a profile between stations Progress and Vostok: PV‑10, NVFL‑1, SW‑42, and the Vostok point). In long annually resolved Na+ records, we had revealed the following periodicities: 17 to 95‑year (Vostok) and 29 to 52‑year (NVFL‑1), while the shorter records are characterized by 8‑year periodicity. The Na+ concentrations decrease as the snow accu‑ mulation increases (especially, at the Vostok station), and this is evidence for a presence of «dilution effect» in the sites with the great part of «dry precipitation». The closest relationship was revealed between changes in flows of Na+ at points SW‑42, and PV‑10. Variability of the Na+ fluxes had been linked to the circulation indices (AAO, PDO, SOI, MEI, SPO) and the sea level pressure in the Southern Hemisphere, as well as to occurrence of Elementary Circulation Mechanisms (ECM). The revealed irregularity of the Na+ precipitation over the area under investigation is caused by different atmospheric circulation patterns as well as by influ‑ ence of basic Action Centers of the Atmosphere (ACA) in the Southern Hemisphere. The closest relationship is found to take place with South Pacific ACA (Vostok, 1976–2009) and with the South Indian ACA (SW‑42 and PV‑10). A presence of distant atmospheric relations (including one with El Nino) had been revealed for the inland areas. Changes in features of the atmospheric circulation in the South Indian Ocean over the last 200‑year period have been reconstructed on the basis of summarized Na+ records from the Vostok station area. Distinctive feature of the atmospheric circulation is the 40‑year periodicity with its increasing intensity during the following periods: 1805–1820, 1830–1860, 1890–1900, 1940–1950, and 1980–2000. In addition, we had revealed that changes in the atmospheric circulation in the Indian Ocean (Southern Hemisphere) were synchronous with similar variability of the circulation in the Siberian (Northern Hemisphere) sector.